ANALYSIS OF STUDENTS 'TRENDS TO OBTAIN LEARNING MOTIVATION THROUGH INDIVIDUAL COUNSELING IN CLASS IX STUDENTS OF SMP N 18 SURAKARTA STUDY YEAR 2020/2021 - Lala Putri Kusumawati; Lydia Ersta Kusumaningtyas; Eko Adi Putro (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
This study aims to determine the results of